16th IEEE Symposium Computer-Based Medical Systems, 2003. Proceedings.
DOI: 10.1109/cbms.2003.1212810
|View full text |Cite
|
Sign up to set email alerts
|

Volumetry of hepatic metastases in computed tomography using the watershed and active contour algorithms

Abstract: The liver is a common site of metastatic disease. Colorectal liver metastases (CLM) alone is diagnosed in approximately 50,000 patients each year in the United States. Treatment for liver metastases is monitored according to the size and number of the hepatic metastases visualized with contrast-enhanced computed tomography (CT). In routine clinical practice, lesion size is assessed according to uni-or bi-dimensional criteria. However, measurements made using these criteria are subject to inter-observer variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…on an organic human liver phantom [8]. CT-based volumetry studies used watershed, active contour and fuzzy c-means algorithms [9,10] and a shape-constraint region growing algorithm to automatically delineate liver metastases on CT images [12]. Seo KS [11] proposed a multi-stage, automatic hepatic tumour segmentation scheme that included liver structure segmentation, removal of hepatic vessels and hepatic tumour extraction by using composite hypotheses and minimal total probability error.…”
Section: Liver Tumour Segmentation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…on an organic human liver phantom [8]. CT-based volumetry studies used watershed, active contour and fuzzy c-means algorithms [9,10] and a shape-constraint region growing algorithm to automatically delineate liver metastases on CT images [12]. Seo KS [11] proposed a multi-stage, automatic hepatic tumour segmentation scheme that included liver structure segmentation, removal of hepatic vessels and hepatic tumour extraction by using composite hypotheses and minimal total probability error.…”
Section: Liver Tumour Segmentation Techniquesmentioning
confidence: 99%
“…Hence automatic, accurate and robust methods for liver tumour segmentation and volumetry are increasingly receiving attention and research efforts from medical imaging, computer vision and pattern recognition communities. Some semiautomated methods, including region growing, isocontour, active contour, watershed, fuzzy cmeans, etc., have been developed and evaluated for liver tumour segmentation and volumetry [8][9][10][11][12][13][14]. Most of these studies suggest that computerised results are comparable to or highly correlated with manual measurement.…”
Section: Introductionmentioning
confidence: 98%
“…There has been very little interest in liver lesion segmentation [4,5]. The work has focused on relatively simple hypodense lesions which are nicely contrasted against the parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that a bias exists between the clinical practice of inferred measurements of hepatic lesions based on onedimensional or two-dimensional criteria and volume measurement analysis [3]. The results of semi-automatic techniques, using watershed and active contours, guarantee the robustness and reliability of these methods compared to manual segmentation ( [4], [5]). …”
Section: Motwationmentioning
confidence: 99%